A Synthetic Route to Sulfobetaine Methacrylates with Varying Charge Distance. Issue 36 (5th November 2014) - Kratzer, Domenic; Barner, Leonie; Friedmann, Christian; Bräse, Stefan; Lahann, Joerg
Abstract: A general synthetic strategy is described that enables access to a library of new sulfobetaine methacrylates starting from commercially available precursors. The three‐step procedure allows the distance between the quaternary amine and the sulfonate group (inner charge distance) to be varied by selecting the corresponding dibromoalkane in the first step. A key step is the final esterification, in which methacrylic acid acts as solvent as well as reagent for the zwitterionic hydroxy intermediates. Thus, it is possible to synthesize monomeric precursors with up to twelve methylene groups between the positive and the negative charge. A selection of these monomers has been successfully tested for their ability to polymerize using free‐radical polymerization. Abstract : A simple and highly universal three‐step procedure has been developed for the synthesis of sulfobetaine methacrylates with variation of the charge separation distance. The protocol provides access to a library of new zwitterionic precursors that have potential for a range of applications in polymer chemistry and materials science.